Meningkatan Keterampilan dalam Pengelolaan Keuangan pada Remaja Kampung Ciwindu - Nabillah; Aisyah; Vio Puspita Sari (Prodi Akuntansi, Universitas Pamulang Kampus Serang, 2025)
Community Service (PKM) in Ciwindu Village, Ciwarna Village, Serang Regency, on October 3-4, 2024 aims to improve the knowledge and skills of adolescents in financial management. The program begins with village observation, followed by planning, execution, and evaluation through surveys, interactive training, and practical socialization. As a result, there was a significant increase in adolescents' understanding of budgets, priority needs, and financial planning. The program successfully equips them with the skills to achieve long-term financial stability, which is expected to improve their economic well-being. Overall, this PKM has a positive impact on individuals and communities, as well as opening up opportunities for similar programs in the future.